Immune Activation: A Link Between Food Insecurity and Chronic Disease in People Living With Human Immunodeficiency Virus. (16th May 2021) - Tamargo, Javier A; Hernandez-Boyer, Jacqueline; Teeman, Colby; Martin, Haley R; Huang, Yongjun; Johnson, Angelique; Campa, Adriana; Martinez, Sabrina S; Li, Tan; Rouster, Susan D; Meeds, Heidi L; Sherman, Kenneth E; et al.
Abstract: Persistent immune activation is a hallmark of human immunodeficiency virus (HIV) infection and thought to play a role on chronic diseases in people with HIV (PWH). Food insecurity is disproportionately prevalent in PWH and is associated with adverse health outcomes. We determined whether food insecurity was associated with increased plasma levels of soluble CD14, CD27, and CD163 in 323 antiretroviral-treated PWH from the Miami Adult Studies on HIV cohort. Nearly half (42.7%) of participants were food insecure, and 85.5% were virally suppressed (<200 copies/mL). Food insecurity was independently associated with higher levels of soluble CD14 and soluble CD27. Very low food security was associated with increased soluble CD163 levels among those with lower CD4 + cell counts. Food insecurity may promote immune activation in PWH, suggesting a biological link between food insecurity and chronic disease among PWH. Improving financial security and access to high-quality diets could reduce the burden of disease in this highly vulnerable population. Abstract : In this study of low-income US minorities, we found that food insecurity was associated with increased levels of immune activation, which suggests a biological link between food insecurity and poor health outcomes among people living with human immunodeficiency virus.